Pluralism in Islamic Law and Its Implications for Contemporary Islamic Education - Zulpandri; Ronaldi; Tamrin Kamal; Sri Wahyuni; Rosniati Hakim; Lutfi Zaki Al Manfaluthi (Solo International Collaboration and Publication of Social Sciences and Humanities, 2026)
Objective: To analyze the view of Islamic law on pluralism and examine the strategy for the implementation of pluralism values in the world of Islamic education, especially in shaping the character of students who are tolerant, inclusive, and ready to live in a multicultural society. Theoretical framework: Based on the teachings of the Qur'an regarding the recognition of plurality as sunnatullah, the concept of rahmatan lil 'alamin, the principle of ukhuwah insaniyah, and an Islamic educational approach oriented to human values, justice, and freedom of thought. This framework is strengthened by the thoughts of moderate Islamic figures such as M. Quraish Shihab, Harun Nasution, and Nurcholish Madjid. Literature review: Reviews the understanding of pluralism in the Qur'an and classical interpretations such as the works of Abdul Wadud Yusuf and Ahmad Al-Shawi, as well as contemporary thinking that explains how pluralism should be understood socio-culturally, not theologically. The literature also highlights the importance of Islamic education as a space for internalizing the value of pluralism through theological, philosophical, juridical, sociological, and psychological foundations. Methods: Using a qualitative approach based on library research, with descriptive-analytical analysis techniques on primary sources such as the Qur'an, classical interpretation, and modern Islamic thought literature. The data were analyzed to identify normative understanding and applicative strategies of pluralism values in Islamic education. Results:  The study found that pluralism is recognized in Islamic law as a social reality that must be respected without equating the theological truths of all religions. Islamic education has an important role in instilling the value of pluralism through an inclusive curriculum, strengthening moderate religious literacy, multicultural teacher training, interfaith dialogue, and creating a peaceful and open academic climate. Implications: Pluralistic Islamic education can form a religious, tolerant, and ready generation to live in a multicultural society, as well as strengthen the integration between Islamic teachings and national values. Novelty: a new approach that integrates the concept of Islamic pluralism with applicative strategies in education, as well as enriching an inclusive and contextual Islamic education discourse.